PENANGANAN SAMPAH LUAR ANGKASA DALAM KERANGKA HUKUM INTERNASIONAL - Mulyana, Budi; Hidayat, Ananty (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2019)
Environmental issues become one of the trends in the phenomenon of international relations that areincreasingly dynamic. These environmental issues not only focus on what is happening in the area ofthe Sea, Land and Air but have crossed the horizon, which is Space. One of the phenomena of thestudy is about space debris.The existence of space debris has become a matter that requires international regulation, consideringthe handling requires cross-country arrangements.This is the impetus of the purpose of this study, namely to find out the condition of the Space in thiscase the issue of space debris and the response of each country to solve the problem of Space debristhrough international regulation.By using qualitative research methods, it can be explained the results of this study show that spacedebris has become an environmental issue in the phenomenon of international relations, the responseof the state is important to be able to produce international regulations aimed at safeguarding theshared earth environment. inside it.